ANALISIS KETIDAKSEIMBANGAN BEBAN DAN RUGI DAYA AKIBAT ARUS NETRAL DI PENYULANG GI GORONTALO BARU - Rifaldi, Mohammad; Mohamad, Yasin; Dongka, Rahmat Hidayat; Tolago, Ade Irawaty; Matoka, Arifin (Foristek, 2025)
The State Electricity Company (PT.PLN Persero) is a company authorized by the government to handle electricity in Indonesia. Distribution lines are an important component in the distribution of electrical power, therefore power losses in distribution lines must be small so that the received electrical power must be close to the transmitted electrical power. This study discusses electrical power losses and load imbalances in the 20 KV medium voltage primary distribution line at the Gorontalo Baru Substation (GOBAR) feeder. The method used in this study is through data collection of load current measurements for each phase, neutral current (N), and neutral conductor resistance (RN) from seven feeders with a total of 297 distribution transformers. The data is processed using the load imbalance equation and active power loss calculations. The analysis is carried out by comparing the imbalance value to the PLN standard (SK ED PLN No. 0017.E/DIR/2014). The results of the study show that the number of transformers in the GOBAR GI feeder that have an imbalance value exceeding the standard limit or in the bad category is 71 transformers and the amount of power losses experienced by the GOBAR GI is 1423.01 kW outside peak load times and for peak load times of 3051.115 kW. Judging from these losses, so that inter-phase load balancing is an important step in increasing the efficiency and reliability of the electric power distribution system.